2 - On Deligitimising Capitalism: The Scourge of Africa and the South - Amin, Samir (Africa Development, 2021)
Contrary to orthodox belief the ongoing economic growth crisis in the West and the perpetual development crisis in Africa derives from the problematic of capitalism. The situation in Africa of high prices, inflation, massive unemployment and stunted growth is just taken as it is and borne painfully but stocially. But all this is due to the structure of capitalism which this paper seeks to explain. Marxian dynamic analysis, founded on the law of value and its role in the accumulation of capital, is the method of analysis employed. I explore results of such in terms of “unequal development” in the context of the asymmetry of the “centre- periphery” dual model. The discussion leads to an analysis of Walras’s general equilibrium model and paradoxical observation that capitalism never experiences a general equilibrium. The “anti-law of value” theories of Walras, Sraffa, and Keynes are analysed as they seek to transfer economic value from the product of labour to the gains of capital. The critiques of Giovani Arrighi are also woven into the critical fabric. Contemporary liberal economists such as Joseph Stiglitz are noted for their lack of full comprehension of the dynamics of the contemporary form of capitalism which although seeking growth tends rather to stagnation in the social context of human alienation. In the end it is globalised finance capital that will prove to be the Archilles's heel of capitalism. It is at this point that the nations of the South should be prepared to delink from the capitalist as a precondition for genuine development. Necessarily this would apply to the nations of Africa.